Mechanobiology of neural development. (October 2020) - Abuwarda, Hamid; Pathak, Medha M.
Abstract: As the brain develops, proliferating cells organize into structures, differentiate, migrate, extrude long processes, and connect with other cells. These biological processes produce mechanical forces that further shape cellular dynamics and organ patterning. A major unanswered question in developmental biology is how the mechanical forces produced during development are detected and transduced by cells to impact biochemical and genetic programs of development. This gap in knowledge stems from a lack of understanding of the molecular players of cellular mechanics and an absence of techniques for measuring and manipulating mechanical forces in tissue. In this review article, we examine recent advances that are beginning to clear these bottlenecks and highlight results from new approaches that reveal the role of mechanical forces in neurodevelopmental processes.